Impact of using different materials, curing regimes, and mixing procedures on compressive strength of reactive powder concrete - A review - Sara, Ahmed; Zahraa, Al-Dawood; Farid, Abed; Mohammad Abdul, Mannan; Mufid, Al-Samarai (Elsevier, 2021)
Reactive powder concrete (RPC) is an ultra-high performance concrete (UHPC) with an enhanced microstructure. Over the past few years, the demand for RPC has increased due to its superior properties. However, RPC is characterized by its low water-to-binder ratio, high cement and silica fume (SF) content, and absence of coarse aggregates which not only harm sustainable development, but also increase the production costs of RPC and generate shrinkage problems. Within this framework, many studies attempted to use different materials to address these problems and produce eco-friendly RPC with similar performance to that of the traditional RPC. The primary objective of this paper is to present an updated review of the literature on the list of materials used for RPC production and assess their viability as partial and full replacement of cement, SF, and quartz sand/ powder to produce ultra-high strength RPC. The effects of employing different curing regimes and mixing procedures on the compressive strength of RPC will also be reviewed. The results highlight that 1) the use of alternative mineral admixtures (glass powder, limestone & phosphorous slag) can successfully replace cement by up to 50%; 2) replacing SF with mineral admixtures such as slag and fly ash is possible and can yield comparable results by monitoring the molar Ca/Si ratio of the mixes; 3) Quartz sand/powder can successfully be replaced with other types of aggregates/fillers (titanium slag, glass sand, glass powder, rice husk ash, etc); 4) Waste steel fibers can yield comparable strength results to that of steel fibers and the hybridization of glass-steel and polypropylene-steel improves the strength compared to steel or other types alone; and 5) Four-stage mixing yields better strength properties (up to 22% enhancement) compared to three-stage mixing, but further research is required to confirm this finding and establish standard guidelines for the mixing of RPC